Polymorphism of HSD17B1 Ser312Gly with Cancer Risk: Evidence from 66, 147 Subjects. (29th February 2016) - Shi, Lijun; Yang, Xue; Dong, Xin; Zhang, Botao
Abstract : Hydroxysteroid (17-beta)dehydrogenase 1( HSD17B1 ) plays a central role in sex steroid hormone metabolism. HSD17B1 polymorphic variants may contribute to cancer susceptibility. Numerous investigations have been conducted to assess the association between HSD17B1 Ser312Gly polymorphism and cancer risk in multiple ethnicities, yet these have produced inconsistent results. We therefore performed this comprehensive meta-analysis to attempt to provide a quality assessment of the association of interest. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate the strength of associations. After a systematic literature search of several major public databases, 20 studies involving 29, 460 cases and 36, 687 controls were included in this meta-analysis. No significant association was found between HSD17B1 Ser312Gly polymorphism and cancer risk. However, Ser312Gly polymorphism showed a significantly decreased risk for Caucasians (there were 44, 284 Caucasians for analysis, comprising 19, 889 cases and 24, 395 controls) in the subgroup analysis by ethnicity (dominant: OR = 0.958, 95% CI = 0.919–0.998; and allele comparing: OR = 0.973, 95% CI = 0.947–0.999). And there was the same trend towards risk in the population-based (PB) controls (homozygous: OR = 0.951, 95% CI = 0.908–0.997 and allele comparing: OR = 0.976, 95% CI = 0.954–0.999), but not among Asians or hospital-based (HB) controls. In addition, no association was observed in the stratified analysis for breast cancer studies by source of control, ethnicity and quality score. These findings suggested that the HSD17B1 Ser312Gly polymorphism might confer genetic cancer susceptibility in an ethnic-dependent manner, especially among Caucasians. Well-designed, large-scale studies are warranted to validate these findings.